Epilepsy surgery in infants up to 3 months of age: Safety, feasibility, and outcomes: A multicenter, multinational study. (14th June 2021) - Roth, Jonathan; Constantini, Shlomi; Ekstein, Margaret; Weiner, Howard L.; Tripathi, Manjari; Chandra, Poodipedi Sarat; Cossu, Massimo; Rizzi, Michele; Bollo, Robert J.; Machado, Hélio Rubens; Santos, Marcelo Volpon; Keating, Robert F.; et al.
Summary: Objective: Drug‐resistant epilepsy (DRE) during the first few months of life is challenging and necessitates aggressive treatment, including surgery. Because the most common causes of DRE in infancy are related to extensive developmental anomalies, surgery often entails extensive tissue resections or disconnection. The literature on "ultra‐early" epilepsy surgery is sparse, with limited data concerning efficacy controlling the seizures, and safety. The current study's goal is to review the safety and efficacy of ultra‐early epilepsy surgery performed before the age of 3 months. Methods: To achieve a large sample size and external validity, a multinational, multicenter retrospective study was performed, focusing on epilepsy surgery for infants younger than 3 months of age. Collected data included epilepsy characteristics, surgical details, epilepsy outcome, and complications. Results: Sixty‐four patients underwent 69 surgeries before the age of 3 months. The most common pathologies were cortical dysplasia (28), hemimegalencephaly (17), and tubers (5). The most common procedures were hemispheric surgeries (48 procedures). Two cases were intentionally staged, and one was unexpectedly aborted. Nearly all patients received blood products. There were no perioperative deaths and no major unexpected permanent morbidities. Twenty‐five percent of patients undergoing hemispheric surgeries developed hydrocephalus. Excellent epilepsy outcome (International League Against Epilepsy [ILAE] grade I) was achieved in 66% of cases over a median follow‐up of 41 months (19–104 interquartile range [IQR]). The number of antiseizure medications was significantly reduced (median 2 drugs, 1–3 IQR, p < .0001). Outcome was not significantly associated with the type of surgery (hemispheric or more limited resections). Significance: Epilepsy surgery during the first few months of life is associated with excellent seizure control, and when performed by highly experienced teams, is not associated with more permanent morbidity than surgery in older infants. Thus surgical treatment should not be postponed to treat DRE in very young infants based on their age.